Predictive bookmaker consensus model for the UEFA Euro 2016 - Achim Zeileis; Christoph Leitner; Kurt Hornik (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
From 10 June to 10 July 2016 the best European football teams will meet in France to determine the European Champion in the UEFA European Championship 2016 tournament (Euro 2016 for short). For the first time 24 teams compete, expanding the format from 16 teams as in the previous five Euro tournaments. For forecasting the winning probability of each team a predictive model based on bookmaker odds from 19 online bookmakers is employed. The favorite is the host France with a forecasted winning probability of 21.5%, followed by the current World Champion Germany with a winning probability of 20.1%. The defending European Champion Spain follows after some gap with 13.7% and all remaining teams are predicted to have lower chances with England (9.2%) and Belgium (7.7%) being the "best of the rest". Furthermore, by complementing the bookmaker consensus results with simulations of the whole tournament, predicted pairwise probabilities for each possible game at the Euro 2016 are obtained along with "survival" probabilities for each team proceeding to the different stages of the tournament. For example, it can be determined that it is much more likely that top favorites France and Germany meet in the semifinal (7.8%) rather than in the final at the Stade de France (4.2%) - which would be a re-match of the friendly game that was played on 13 November 2015 during the terrorist attacks in Paris and that France won 2-0. Hence it is maybe better that the tournament draw favors a match in the semifinal at Marseille (with an almost even winning probability of 50.5% for France). The most likely final is then that either of the two teams plays against the defending champion Spain with a probability of 5.7% for France vs. Spain and 5.4% for Germany vs. Spain, respectively. All forecasts are the result of an aggregation of quoted winning odds for each team in the Euro 2016: These are first adjusted for profit margins ("overrounds"), averaged on the log-odds scale, and then transformed back to winning probabilities. Moreover, team abilities (or strengths) are approximated by an "inverse" procedure of tournament simulations, yielding estimates of probabilities for all possible pairwise matches at all stages of the tournament. This technique correctly predicted the winner of the FIFA 2010 and Euro 2012 tournaments while missing the winner but correctly predicting the final for the Euro 2008 and three out of four semifinalists at the FIFA 2014 World Cup (Leitner, Zeileis, and Hornik 2008, 2010a,b; Zeileis, Leitner, and Hornik 2012, 2014).
Keywords: C53; C40; D84; 330; consensus; agreement; bookmakers odds; tournament; UEFA European Championship 2016